Workshop Mobile Learning Mastery: Optimalisasi Aplikasi Mikro Edukasi dalam Meningkatkan Kemandirian Belajar Siswa SMA Koperasi Pontianak - Maulana Filani Rizal; Dami; Irvan Wibowo (Irajagaddhita, 2026)
The "Mobile Learning Mastery" workshop conducted as part of a community service initiative serves as a strategic effort to equip students and educators with both technical and methodological skills. By leveraging micro-education applications, the activity aims to shift the student paradigm from passive content consumers to active learners capable of productively managing their digital ecosystems. The synergy between mobile technology and learner autonomy is expected to foster a culture of lifelong learning that adapts to the demands of the times. The initiative aims to provide training on the effective use of learning technology to high school students, enabling them to study effectively and prepare for a brighter future. A participatory training method was employed, actively involving students in both theoretical sessions and practical exercises regarding financial planning. The training material covered budget management, saving, and an accessible introduction to capital market investments, all tailored to the students' needs and level of understanding. Data were collected via pre-test and post-test questionnaires to measure improvements in student understanding, alongside observations during the training to assess participant engagement and responsiveness. The results indicate a significant improvement in students' knowledge and skills regarding the learning process following the training, evidenced by a marked increase in average post-test scores compared to pre-test scores. The training proved effective in equipping students with fundamental learning capabilities that support their independence and readiness to face future global challenges.